Serum metabolomics reveals that arsenic exposure disrupted lipid and amino acid metabolism in rats: a step forward in understanding chronic arsenic toxicity. Issue 3 (20th February 2015) - Wang, Xiaoxue; Mu, Xiaoli; Zhang, Jie; Huang, Qingyu; Alamdar, Ambreen; Tian, Meiping; Liu, Liangpo; Shen, Heqing
Abstract : Chronic arsenic exposure induces metabolome disruption in rat. Abstract : Chronic arsenic exposure through drinking water threatens public health worldwide. Although its multiorgan toxicity has been reported, the impact of chronic arsenic exposure on the metabolic network remains obscure. In this study, male Sprague Dawley rats were exposed to 0.5, 2 or 10 ppm sodium arsenite for three months. An ultra-high performance liquid chromatography/mass spectrometry based metabolomics approach was utilized to unveil the global metabolic response to chronic arsenic exposure in rats. Distinct serum metabolome profiles were found to be associated with the doses. Eighteen differential metabolites were identified, and most of them showed dose-dependent responses to arsenic exposure. Metabolic abnormalities mainly involved lipid metabolism and amino acid metabolism. The metabolic alterations were further confirmed by hepatic gene expression. Expressions of cpt2, lcat, cact, crot and mtr were significantly elevated in high dose groups. This study provides novel evidence to support the association between arsenic exposure and metabolic disruption, and it contributes to understanding the mechanism of chronic arsenic toxicity.